Persepsi Masyarakat Lokal terhadap Eko Turisme di Desa Ketingan, Yogyakarta, - Pandu Adi Cakranegara (Jurnal Kajian Pariwisata, 2019)
Abstract In Indonesia there are many eco-tourism objects. However only a small amount of places that managed to attract tourists. This research is studying an eco-tourism object in one of villages in Jogjakarta. By using local perception as a point of view researcher is trying to find how local people are affected by tourism. This paper is following the framework of Tourism Area Life Cycle. The perception measurement are using questionnaires develop previous researcher. The total populations of Ketingan Village are 40 households. The samples taken are 30 households. Respondent are filling questionnaire and there are short interviews done. The perception before tourism object developed and after tourism object developed is compared using t-test for mean difference. There are four hypotheses, those are: 1.There are significant differences between respondents' perceptions of local people before ecotourism and after ecotourism in terms of economic factor sustainability, 2. There are significant differences between respondents' perceptions of local people before ecotourism and after ecotourism in terms of sustainability of socio-cultural factors, 3.There are significant differences between the perceptions of respondents of local people before ecotourism and after ecotourism in terms of environmental sustainability, 4. There are significant differences between respondents' perceptions of local people before ecotourism and after ecotourism in terms of sustainability of life satisfaction factors. The findings of this research are that there are significant difference in perception in economics, social and cultural and quality of life. However there are no significant differences in perception toward environment. The eco-tourism is not managed to increase the well-being of the local people but it does not harm the environment. Key Words: tourism; perception; eco-tourism Di Indonesia ada banyak obyek ekowisata. Namun hanya sejumlah kecil tempat yang berhasil menarik wisatawan. Penelitian ini mempelajari objek ekowisata di salah satu desa di Yogyakarta. Dengan menggunakan persepsi lokal sebagai sudut pandang, peneliti berusaha menemukan bagaimana masyarakat lokal dipengaruhi oleh pariwisata. Makalah ini mengikuti kerangka siklus hidup bidang pariwisata. Pengukuran persepsi menggunakan kuesioner yang dikembangkan peneliti sebelumnya. Total populasi Desa Ketingan adalah 40 rumah tangga. Sampel yang diambil adalah 30 rumah tangga. Responden mengisi kuesioner dan ada wawancara singkat yang dilakukan. Persepsi sebelum objek wisata dikembangkan dan setelah objek wisata dikembangkan dibandingkan dengan menggunakan uji-t untuk perbedaan rata-rata. Ada empat hipotesis, yaitu: 1. Ada perbedaan yang signifikan antara persepsi responden tentang masyarakat lokal sebelum ekowisata dan setelah ekowisata dalam hal keberlanjutan faktor ekonomi, 2. Ada perbedaan yang signifikan antara persepsi responden terhadap masyarakat lokal sebelum ekowisata dan setelah ekowisata dalam hal keberlanjutan faktor sosial budaya, 3. Ada perbedaan yang signifikan antara persepsi responden masyarakat lokal sebelum ekowisata dan setelah ekowisata dalam hal kelestarian lingkungan, 4. Ada perbedaan yang signifikan antara persepsi responden terhadap masyarakat lokal sebelum ekowisata dan setelah ekowisata dalam hal keberlanjutan faktor kepuasan hidup. Temuan penelitian ini adalah terdapat perbedaan persepsi yang signifikan dalam ekonomi, sosial dan budaya dan kualitas hidup. Namun tidak ada perbedaan persepsi yang signifikan terhadap lingkungan. Ekowisata tidak dikelola untuk meningkatkan kesejahteraan masyarakat setempat tetapi tidak merusak lingkungan. Kata Kunci: pariwisata; persepsi; ekowisata